Metabolites dynamics and fruit production during the guarana harvest (Research, Society and Development, 2022)
Guarana from the Amazon is used in human supplementation mainly due to the presence of methylxanthines and polyphenols represented by caffeine (CF), theobromine (TB), catechin (CT) and epicatechin (EP), which provide energy and antioxidant properties to its products based on of the seeds. The fructification of the guarana tree is not standardized, making the harvest expensive, as it is carried out manually and in a staggered way. Thus, the objective was to investigate fruit production and the content of CF, TB, CT and EP throughout the 2017 harvest. Fruit production was analyzed daily and 12 harvests were carried out at an interval of 63 days, only Ripe and open fruits. Methylxanthines and polyphenols were quantified by high performance liquid chromatography (HPLC) from selected fruits from five harvest times, with an interval of 14 days. The amounts of CT, EP and TB were higher when the first fruits ripened. Caffeine, on the other hand, remained practically stable throughout the evaluated period. In the first four weeks, the harvest had to be carried out twice a week, from then on, weekly. Subsequently, only one harvest per week was required until the end of the season. The amount of fruits harvested in each harvest changed and also reached a peak of productivity in the tenth harvest, after 104 days of pollination.